ANALISIS KEBERAGAMAN USAHA RUMAHT ANGGA PERTANIAN DI LAHAN MARJINAL - Dewa K.S Swastika; Roosganda Elizabeth; Juni Hestina (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2007)
Most of farmers in Indonesia, especially in marginal land. are small scale farmers with limited resources. These limitations have caused low level of technology application, thus low productivity and low income. To meet their household consumption. they have to find other job for additional income earning. This study is aimed to: (1) to assess the model offarming system, (2) to evaluate the variability of household's income, (3) to assess the contribution of on-farm, off-farm and non-farm incomes on the total household's income, and (4) to assess the degree of relationship between household characteristic and job variability. The study was conducted in three marginal land, namely: rain-fed in WestJava, dry-land in Bali, and swampy land in WestKalimantan. The results showed thatfarmers in rain-fed of WestJava and swampy land of WestKalimantan were doing partial farming, whilefarmers in dryland of Bali were doing integrated farming system. Farmers in these three agroecosystem were diversified in sources of income. On-farm was the highest source of household's income,followed by non-farm and off-farm. However, there is no significant correlation betweenjob diversification and level ofhousehold's income. It might be that thejob diversification was mainly done by small farmers whose on-farm income alone could not meet their household's consumption. Meanwhile, largefarmers did lessjob. Hence, at the end their household's income was not significantly different. The high contribution of agricultural sector on household's income indicated its high role on rural economy. Therefore, this sector should be developed in an integrated development, includedfarming system development,partnership betweenfarmers and private sector, gro-industrial development, and infrastructure development. It is expected that these integrated development will create marketfor agricultural products, job opportunity for rural people, and finally will improve household's income and welfare.